Charting recent development in computer assisted language learning - Zaphiris, Panayiotis; Ioannou, Andri; Papadima-Sophocleous, Salomi; Parmaxi, Antigoni (My University, 2013)
This paper charts the research development in Computer Assisted Language Learning (CALL), by building a framework of existing research work in the field. Based on a corpus of 163 articles, published between January 2009 and September 2010 in four major journals devoted to CALL, it sets out to describe the range of topics covered under the umbrella of CALL. The approach adopted in this research includes (a) development of the 2009-2010 CALL corpus; (b) literature overview and extraction of codes from the 2009-2010 CALL corpus; (c) refinement of the extracted codes through focus group and construction of the CALL chart Version 1.0 based on the elaborated coding scheme; (d) refinement of the CALL chart Version 1.0 following a systematic approach of content analysis and development of the CALL chart Version 2.0; and finally (e) card sorting evaluation of the proposed structure and inclusiveness of all categories in the CALL chart Version 2.0 which lead to (f) the development of the CALL chart Version 3.0. The research trends in the major categories of the CALL chart are discussed, as well as possible future directions in the field